Implementation of French Recommendations for the Prevention and the Treatment of Hospital-acquired Pneumonia: A Cluster-randomized Trial. (24th September 2020) - Roquilly, Antoine; Chanques, Gérald; Lasocki, Sigismond; Foucrier, Arnaud; Fermier, Brice; De Courson, Hugues; Carrie, Cedric; Danguy des Deserts, Marc; Gakuba, Clément; Constantin, Jean-Michel; Lagarde, Kevin; Holleville, Mathilde; et al.
Abstract: Background: We determined whether an audit on the adherence to guidelines for hospital-acquired pneumonia (HAP) can improve the outcomes of patients in intensive care units (ICUs). Methods: This study was conducted at 35 ICUs in 30 hospitals. We included consecutive, adult patients hospitalized in ICUs for 3 days or more. After a 3-month baseline period followed by the dissemination of recommendations, an audit on the compliance to recommendations (audit period) was followed by a 3-month cluster-randomized trial. We randomly assigned ICUs to either receive audit and feedback (intervention group) or participate in a national registry (control group). The primary outcome was the duration of ICU stay. Results: Among 1856 patients enrolled, 602, 669, and 585 were recruited in the baseline, audit, and intervention periods, respectively. The composite measures of compliance were 47% (interquartile range [IQR], 38–56%) in the intervention group and 42% (IQR, 25–53%) in the control group ( P = .001). As compared to the baseline period, the ICU lengths of stay were reduced by 3.2 days in the intervention period ( P = .07) and by 2.8 days in the control period ( P = .02). The durations of ICU stay were 7 days (IQR, 5–14 days) in the control group and 9 days (IQR, 5–20 days) in the intervention group ( P = .10). After adjustment for unbalanced baseline characteristics, the hazard ratio for being discharged alive from the ICU in the control group was 1.17 (95% confidence interval, .69–2.01; P = .10). Conclusions: The publication of French guidelines for HAP was associated with a reduction of the ICU length of stay. However, the realization of an audit to improve their application did not further improve outcomes. Clinical Trials Registration: NCT03348579. Abstract : Compared to participation in a national registry, audit and feedback on applications of national recommendations for hospital-acquired pneumonia did not reduce durations of intensive care unit stays, although the implementation of independent, nonaudit recommendations was associated with shorter stays.